2022
DOI: 10.1101/2022.06.17.22276575
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Change in Effectiveness of Sotrovimab for Preventing Hospitalization and Mortality in COVID-19 Outpatients During the Omicron Phase

Abstract: Background: Sotrovimab, a neutralizing monoclonal antibody (mAb) treatment authorized for early symptomatic COVID-19 patients, was effective in preventing the progression of severe disease and mortality following SARS-CoV-2 Delta variant infection. It is not known whether sotrovimab is similarly effective for SARS-CoV-2 Omicron variant infection. Methods: Observational cohort study of non-hospitalized adult patients with SARS-CoV-2 infection from December 26, 2021 to March 10, 2022 (>96% Omicron BA.1 vari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Data are available online for the included studies. 19,20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]…”
Section: Author Contributionsmentioning
confidence: 99%
“…Data are available online for the included studies. 19,20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]…”
Section: Author Contributionsmentioning
confidence: 99%
“…While some mAbs have lost effectiveness due to resistance of newer variants [10,11], other mAb agents and antivirals have maintained effectiveness. When these agents are effective, hospitalization or death (e.g., treatment failure) occurs infrequently but are important outcome measures to understand which patients might be less likely to benefit from mAb therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Among 522 sotrovimab-treated patients PS-matched with 1,563 patients not treated with a mAb, sotrovimab treatment was associated with a 63% (OR: 0.37; 95% CI: 0.19, 0.66) lower odds of 28-day all-cause hospitalization and an 89% (OR: 0.11; 95% CI: 0.0, 0.79) lower odds of 28-day all-cause mortality, similar to our findings during the time period when Delta was the predominant variant (Aggarwal et al, 2022a). A subsequent study using similar methods assessed sotrovimab effectiveness among 5,205 PS-matched high-risk patients between December 26, 2021, and March 10, 2022, and found non-significant lower odds of 28-day all-cause hospitalization (OR: 0.82, 95% CI: 0.55, 1.19) and 28-day all-cause mortality (OR: 0.62, 95% CI: 0.07, 2.78) during the Omicron BA.1 wave (Aggarwal, et al, 2022b). In contrast, our findings showed that sotrovimab maintained statistically significant lower odds of 30-day all-cause hospitalization or mortality between 55%-67% during the December 2021 through March 2022 time period when Omicron BA.1 became the predominant circulating variant.…”
Section: Discussionmentioning
confidence: 99%
“…Among high-risk subgroups, Aggarwal, et al observed trending towards a lower odds of 28-day hospitalization among patients age ≥65 years (OR: 0.52, 95% CI: 0.30, 0.92), immunocompromised patients (OR: 0.63, 95% CI: 0.38, 1.04), and those with 2 or more comorbid conditions (OR: 0.65, 95% CI: 0.42, 1.01) who were treated with sotrovimab compared with those not treated with a mAb. The non-significant findings from Aggarwal, et al may be due to the smaller sample size and lower power to detect differences between treatment groups (Aggarwal, et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%